2022
DOI: 10.1002/adts.202200207
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Defects in Cs2SnI6‐Based Double Perovskite Solar Cells Via SCAPS‐1D

Abstract: Effective conversion of solar photons into electrical power through the development of smart and eco‐friendly materials is one of the most extensively researched methods for generating renewable energy. In this work, an inorganic lead‐free double perovskite Cs2SnI6 material is employed as an active layer for solar cell applications, together with GO (graphene oxide) as electron transport layer (ETL) and Cu2O as hole transport layer (HTL). In order to find the most efficient photovoltaic device, a detailed theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
(91 reference statements)
0
25
0
Order By: Relevance
“…The initial proposed structure has material parameters, which are listed in Table 2, layer defects in Table 3, and interfacial defects described in Table 4. All the essential parameters used in this theoretical study have been derived from existing literature as follows: FTO, [38] TiO 2 , [39] Cs 2 SnI 6 , [35,36,[40][41][42] and Cu 2 O. [43,44] Moreover the other material parameters used for ZnO, CdS, and P3HT in the simulation have been summarized in Table S1 of the Supporting Information.…”
Section: Device Architecture and Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial proposed structure has material parameters, which are listed in Table 2, layer defects in Table 3, and interfacial defects described in Table 4. All the essential parameters used in this theoretical study have been derived from existing literature as follows: FTO, [38] TiO 2 , [39] Cs 2 SnI 6 , [35,36,[40][41][42] and Cu 2 O. [43,44] Moreover the other material parameters used for ZnO, CdS, and P3HT in the simulation have been summarized in Table S1 of the Supporting Information.…”
Section: Device Architecture and Input Parametersmentioning
confidence: 99%
“…An optimized FTO/graphene oxide/Cs 2 SnI 6 /Cu 2 O/Au configuration was employed to obtain maximum theoretical parameters of V OC = 0.837 V, J SC = 34.6 mA cm −2 , FF = 81.64%, and η = 23.64% considering a total 10 14 cm −3 defect density. [ 35 ] A solar cell utilizing the same architecture, at the same defect concentration was demonstrated to have an optimum V OC = 1.0 V, J SC = 25.93 mA cm −2 , FF = 29.57%, and η = 7.73%. [ 36 ] The discrepancies in theoretical results and experimental values should be tackled in order to gain an in‐depth understanding of the physics behind the operation of perovskite material based solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…As doping concentration increases, built‐in potential ( V bi ) rises, and reverse saturation current decreases, so significant enhancement in V OC is observed in devices without bilayers ( Figure 5 ), which is mathematically justified by Equations (9), (12), and (14). [ 23,36 ] This improved V bi also resulted in directional charge transport and lower recombinations. Built‐in potential and I 0 can be expressed asVbi=Vtln(NANnormalDni2)I0=qni2(DnLnNnormalA+DnormalpLnormalpNnormalD)…”
Section: Resultsmentioning
confidence: 99%
“…53 The presence of bulk, as well as surface defects inside a solar device, plays a crucial role in solar cell efficiency. 54 discharge lamp with a semiconductor having bandgap 2.10 eV. 12 The upper PCE limit for fluorescent tube and sodium lamp were observed to be 46% and 67% respectively.…”
Section: 𝑶𝑪mentioning
confidence: 99%
“…53 The presence of bulk, as well as surface defects inside a solar device, plays a crucial role in solar cell efficiency. 54 While bulk defects mainly contribute toward SRH or trap-assisted recombination, excess surface defects deteriorate solar cell performance by hampering the collection carriers. Ryu et al observed a diminishing of charge carrier trapping due to defects while increasing the intensity of light from 0.01 sun to 1 sun conditions while using MAPbI 3 -based solar cells.…”
Section: Features Of Ipvsmentioning
confidence: 99%